2007
DOI: 10.1097/qad.0b013e328013d9b5
|View full text |Cite
|
Sign up to set email alerts
|

PRO 2000 elicits a decline in genital tract immune mediators without compromising intrinsic antimicrobial activity

Abstract: In contrast to experience with nonoxynol-9, PRO 2000 did not trigger an inflammatory response in cervicovaginal secretions. There was a modest reduction in mucosal immune mediators, but this loss was not associated with a reduction in intrinsic antimicrobial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
140
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(153 citation statements)
references
References 31 publications
11
140
2
Order By: Relevance
“…That uterine hormone-induced protection is crucial to reproductive health is further supported by the findings at midcycle, when E 2 levels are elevated, that cervical-vaginal concentrations of antimicrobials as well as cytokines/ chemokines decline by 10-to 100-fold. 31 In addition to preparing the upper FRT for implantation, our findings of enhanced antimicrobial production in the uterus further suggest that midcycle secretions from the Fallopian tubes and uterus, by draining into the cervix and vagina, provide innate protection to the lower FRT when local immune protection is suppressed.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…That uterine hormone-induced protection is crucial to reproductive health is further supported by the findings at midcycle, when E 2 levels are elevated, that cervical-vaginal concentrations of antimicrobials as well as cytokines/ chemokines decline by 10-to 100-fold. 31 In addition to preparing the upper FRT for implantation, our findings of enhanced antimicrobial production in the uterus further suggest that midcycle secretions from the Fallopian tubes and uterus, by draining into the cervix and vagina, provide innate protection to the lower FRT when local immune protection is suppressed.…”
Section: Discussionmentioning
confidence: 70%
“…[27][28][29][30] We and others have found that a number of cytokines, chemokines, and antimicrobials in cervical-vaginal lavage vary with stage of the menstrual cycle. 31,32 Relative to that measured during the early proliferative and late secretory phases of the menstrual cycle, concentrations of SLPI, defensins, IL-8, and so on are lowest at midcycle when ovulation occurs and estradiol levels are known to be elevated. In studies with isolated polarized epithelial cells, we previously demonstrated that apical secretions from polarized human UECs from the premenopausal women, but not from postmenopausal women, were antibacterial against both Gram-positive and Gram-negative bacteria; antibacterial activity was partially neutralized with antibody to SLPI.…”
Section: Introductionmentioning
confidence: 98%
“…35 Administration of PRO 2000 resulted in no loss of anti-HSV, anti-HIV, or antibacterial activity in the CVL. 37 In this study, antiviral testing suggested that CS retained its antiviral activity in the vaginal environment for at least 8-18 h after dosing and had no apparent detrimental effect on endogenous defenses after dosing was discontinued. A limitation of our study is that we did not measure CS levels in the CVLs.…”
Section: Vaginal Safety Of Cs Hec Placebo and N-9mentioning
confidence: 99%
“…A limitation of our study is that we did not measure CS levels in the CVLs. Antiviral activity was seen to persist in the vaginal environment of PRO 2000 37 and tenofovir 40 users; in those studies, levels of drug in the CVL were measured.…”
Section: Vaginal Safety Of Cs Hec Placebo and N-9mentioning
confidence: 99%
See 1 more Smart Citation